Chapter Tactical Communications for Cooperative SAR Robot Missions - Sanchez, Jose (InTechOpen, 2017)
This chapter describes how the ICARUS communications (COM) team defined, developed and implemented an integrated wireless communication system to ensure an interoperable and dependable networking capability for both human and robotic search and rescue field teams and crisis managers. It starts explaining the analysis of the requirements and the context of the project, the existing solutions and the design of the ICARUS communication system to fulfil all the project needs. Next, it addresses the implementation process of the required networking capabilities, and finally, it explains how the ICARUS communication system and associated tools have been integrated in the overall mission systems and have been validated to provide reliable communications for real‐time information sharing during search and rescue operations in hostile conditions.